ANALYSIS OF THE EXISTENCE OF INSPECTION ROADS TO ENSURE FLIGHT SAFETY AND SECURITY AT THE BLU OFFICE OF THE MAIN CLASS 1 UPBU JUWATA TARAKAN - Nurfadhilah, Siti; Bondan Ramadha, Dadang; Musadek, Ahmad (Proceeding of International Conference of Advanced Transportation, Engineering, and Applied Social Science, 2025)
This research analyzes the existence and effectiveness of the inspection road in ensuring flight safety and security at Juwata Tarakan Airport. The background to the problem is the inadequate inspection road infrastructure, especially at the end of runway 06 which is still a swamp, thereby hindering perimeter fence patrols and emergency response. The objective of this study is to evaluate the physical condition, supporting facilities, and the role of the inspection road in airport security operations. The method used is a qualitative approach with an interview technique involving three Aviation Security (Avsec) personnel who work at Juwata Tarakan Airport. The results show that the existing inspection roads do not meet the standards, and supporting facilities such as CCTV and lighting are not complete. Nevertheless, the inspection road is considered very important and effective for perimeter patrols and for accelerating emergency responses, especially in areas that are difficult to reach. Based on the findings, it can be concluded that although the current inspection road supports work at several points, it is still not optimal overall. The suggestions put forward are to immediately realize the comprehensive construction of the inspection road, especially in the runway 06 area, improve supporting infrastructure and facilities, and carry out periodic maintenance to ensure sustainable flight safety.